Pengembangan Buku Cergam dalam Meningkatkan Kemampuan Bahasa Anak Usia 5-6 Tahun di TK IT Al-Khalish Kecamatan Medan Labuhan - Indah Warandah; Arlina Arlina; Enny Nazrah Pulungan (ALSYS, 2025)
This study is motivated by the need for innovative learning media to enhance early childhood language skills. One such effort is the development of a picture storybook (CerGam) designed to foster children’s language abilities. The objectives of this research are to determine: (1) the feasibility of the CerGam book in improving children’s language skills, (2) its practicality of use, and (3) its effectiveness for children aged 5–6 years at TK IT Al-Khalish. The study employed a Research and Development (R&D) method using the 4D model, involving 15 children as the sample. Data were collected through validation sheets, practicality questionnaires, and language skill tests, then analyzed using validity, practicality, and effectiveness tests. The findings reveal a significant improvement in children’s language abilities after using the CerGam book. These results affirm that CerGam is feasible, practical, and effective as a learning medium, while also contributing to teachers and parents in supporting early childhood language development.